Differences in the blocking and controlling effects of nine formulated soil conditioners on cadmium content in rice and soil based on experiments in middle and late rice - Xiao, Jingshang; Hou, Hongqian; Ji, Jianhua; Lv, Zhenzhen; Lan, Xianjin; Liu, Yiren; Liu, Xiumei; Huang, Xiaonian; Qian, Long; Rong, Qinlei; Zhou, Lijun (Frontiers in Agronomy, 2026)
Heavy metal contamination has emerged as a critical constraint on agricultural productivity and food security, particularly in Cd-contaminated paddy soils. The application of low-cost soil conditioners offering passivation-based immobilization of heavy metals represents a viable remediation strategy. In this study, four amendments (lime, Ca–Mg–P fertilizer, zeolite, and sodium humate) were systematically evaluated through a uniform experimental design (U9 matrix) comprising nine treatments under field conditions. This study found that the optimal soil conditioner formulation (T3) is lime/Ca–Mg–P fertilizer/sodium humate = 1:5:0.58. Among all treatments, T3 exhibited superior remediation efficacy, achieving reductions of 33.81% and 29.75% in soil bioavailable Cd during middle and late rice cultivation, respectively. This treatment reduced grain Cd concentrations by 59.69% and 51.26% in middle and late rice crops, respectively, while simultaneously enhancing grain yields by 15.2% and 12.5%. Furthermore, T3 application significantly decreased Cd enrichment factors (BCF) and translocation factors (TF) in rice organs, particularly in roots (37.22%), stems (47.07%), leaves (52.47%), and grains (59.69%) of middle rice. Finally, soil conditioner application can reduce the available Cd content of acidic Cd-contaminated rice soils in the middle and late rice seasons and regulate the enrichment factor and the translocation factor of rice soil Cd in various rice organs. The optimized amendment formulation (lime/Ca–Mg–P fertilizer/sodium humate = 1:5:0.58) effectively regulated Cd bioavailability through pH-mediated speciation changes and competitive ion interactions, demonstrating exceptional potential for achieving dual objectives of yield enhancement and food safety assurance in acidic Cd-contaminated paddy systems.